ASAS-ASAS DALAM HUKUM PIDANA (Kajian Konseptual Terhadap Prinsip-Prinsip Dasar Hukum Pidana) - Aida Dewi Agustina; Laila Fauziah; Yudi Krismen (STKIP Subang, 2026)
Criminal law is an essential component of the legal system that regulates prohibited acts and determines sanctions for offenders. The implementation of criminal law cannot be separated from the fundamental principles that serve as its foundation. This article aims to analyze the basic principles in criminal law, including the principle of legality, culpability, territoriality, nationality, universality, equality before the law, presumption of innocence, ultimum remedium, lex specialis derogat legi generali, and non-retroactivity. This study uses a normative juridical method by examining legal literature, statutory regulations, and relevant scholarly journals. The results show that these principles play a crucial role in ensuring legal certainty, justice, and the protection of human rights in the enforcement of criminal law. Furthermore, the development of modern criminal law demonstrates the need for a dynamic interpretation of these principles in order to respond to contemporary legal challenges, such as transnational crimes and technological advancements. Therefore, a comprehensive understanding and consistent application of criminal law principles are necessary to achieve a fair, effective, and accountable legal system.